(untitled) (XXI Century. Spanish Literature and Culture, 2024)
The novels El Evangelio (2021) by Elisa Victoria and Supersaurio (2022) by Meryem El Mehdati are recent results of the phenomenon of repoliticization that began in the Spanish novel after the economic crisis of 2008 and the 15M movement. In the present study, it is proposed an analysis of both works with the aim of deepening the thematic and formal techniques used to denounce the precariousness of the Spanish youth of the 21st century, a consequence of the current socioeconomic system. Thus, we delve into the political substratum of three literary strategies: the setting of the plots in the workplace, the recurrence of the journey to work and the structuring of the story through the novel-diary.